A Conversation with Professor Ted Kaptchuk, a Key Architect of Modern TCM in the West - Ioannis Solos; Charles Buck; Ted Kaptchuk; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. The interview was conducted on November 20th, 2022 by Ioannis Solos and Charles Buck. Ted Kaptchuk (泰开阳) is a Professor of Medicine and a Professor of Global Health & Social Medicine at Harvard Medical School. In 1975, he graduated from the Macau Institute of Chinese Medicine, Macau, China. After returning to the West, Ted taught Chinese medicine throughout the States, Europe, Latin America, and Australia. Ted's book, The Web that Has No Weaver: Understanding Chinese Medicine is a groundbreaking explanation of East Asian medicine that continues to shape the discourse of the Chinese medicine profession in the West and has been translated into 13 languages. In 1990, Ted was recruited in Harvard Medical School to help research Chinese medicine. After encountering high placebo responses in multiple acupuncture clinical trials, Ted decided to switch his career to primarily studying placebo. He has published over 300 peer-reviewed articles. He has been awarded the Lifetime Achievement Award from the Society of Acupuncture Research (2015), the Lifetime Achievement Award from the Society for Interdisciplinary Placebo Studies (2021), and the William Silen Lifetime Achievement Award in Mentoring from Harvard Medical School (2022).